2020
DOI: 10.2147/rmhp.s275400
|View full text |Cite
|
Sign up to set email alerts
|

<p>Challenges Faced by Multidrug-Resistant Tuberculosis Patients in Three Financially Affluent Chinese Cities</p>

Abstract: Purpose The aim of this study was to analyze socioeconomic burdens and other difficulties that multidrug-resistant tuberculosis (MDR-TB) patients in cities are facing, to identify major obstacles and which groups of patients are most affected. Methods Face-to-face and phone-call interviews were conducted in early 2018 to follow-up with patients newly diagnosed with MDR-TB in 2017 in three tuberculosis hospitals in three financially affluent Chinese cities. Demographic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 24 publications
(31 reference statements)
0
4
0
Order By: Relevance
“…17,18 Previous study from our team showed that average out-of-pocket expense for an MDR-TB patient was about US$300 per month in Shenzhen city. 19 This amounts to nearly half of average monthly income based on a reported GDP per capita of…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17,18 Previous study from our team showed that average out-of-pocket expense for an MDR-TB patient was about US$300 per month in Shenzhen city. 19 This amounts to nearly half of average monthly income based on a reported GDP per capita of…”
Section: Discussionmentioning
confidence: 99%
“… 17 , 18 Previous study from our team showed that average out-of-pocket expense for an MDR-TB patient was about US$300 per month in Shenzhen city. 19 This amounts to nearly half of average monthly income based on a reported GDP per capita of USD7808 in 2018. 20 Our study established a direct relationship between treatment adherence and household income.…”
Section: Discussionmentioning
confidence: 99%
“…In general, MDR TB patients have gone through the long-term medication method with quite a long period of time taking medicines ( Table I ). Because they require medication consistency, both TB patients and MDR TB patients together with their family can experience exhaustion and not small mental pressure ( 21 , 22 ) as well as stressful events ( 23 ). TB patients have the risk to fall into medication failure, and so do the MDR TB patients because the essence of medication lies in the compliance ( 24 , 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…The financial costs of TB can force patients (particularly internal migrants) to remain undiagnosed and untreated, leading to prolonged transmission of MDR-TB. [19][20][21][22] Changes in coverage and reimbursement policies have helped alleviate these financial difficulties, which may partially explain the increase in the proportion of patients enrolled on treatments (from 49.4% in 2012 to 70% in 2017). This financing policy may further improve MDR-TB treatment compliance and outcomes, leading to lower ongoing MDR-TB transmissions in Shenzhen.…”
Section: Discussionmentioning
confidence: 99%